Role of serum procalcitonin in the diagnosis and monitoring of treatment response in treatment-naïve subjects with chronic pulmonary aspergillosis - Sehgal, Inderpaul Singh; Dhooria, Sahajal; Sachdeva, Naresh; Rudramurthy, Shivaprakash M.; Prasad, Kuruswamy Thurai; Muthu, Valliappan; Aggarwal, Ashutosh Nath; Garg, Mandeep; Chakrabarti, Arunaloke; Agarwal, Ritesh (Heliyon, 2023)
Interferon-gamma (IFN-γ) down-regulates plasma procalcitonin (PCT), marker of inflammation. Chronic pulmonary aspergillosis (CPA) is associated with low IFN-γ levels. Thus, plasma PCT may be elevated in CPA and could have a role in diagnosing and monitoring treatment response in CPA. Herein, we investigate the diagnostic performance of plasma PCT in CPA. We extracted the demographic, clinical, radiological, treatment outcomes, and plasma PCT levels of CPA subjects and controls (previously treated pulmonary tuberculosis with radiological abnormalities on CT chest [diseased controls] and treatment naïve active pulmonary tuberculosis [PTB]). We treated CPA subjects with six months of oral itraconazole. We took 0.25 ng/mL as a cut-off value for PCT. The study’s primary objective was to ascertain the diagnostic performance of PCT in diagnosing CPA. The key secondary outcome was to study the change in the plasma PCT levels after itraconazole therapy. We included 190 CPA cases and 40 controls (diseased controls [n = 20] and active PTB [n = 20]). PCT was elevated (≥0.25 ng/mL) in only 7 (3.7%) subjects with CPA. The sensitivity and specificity of PCT (≥0.25 ng/mL) were 3.7% (1.5–7.4%) and 100 (91.2–100%), respectively. The area under the curve for plasma PCT was 0.48 (95% confidence interval, 0.39–0.58). The plasma PCT values were available in 93 subjects at six months. There was a significant decline in the median plasma levels of PCT after treatment; however, the PCT levels either increased or remained the same in 45% of the subjects. Plasma procalcitonin has poor performance in diagnosing and following subjects with CPA.